2017
DOI: 10.1021/acs.jafc.7b04220
|View full text |Cite
|
Sign up to set email alerts
|

Halloysite Tubes as Nanocontainers for Herbicide and Its Controlled Release in Biodegradable Poly(vinyl alcohol)/Starch Film

Abstract: Commercial herbicide atrazine (AT) was first loaded into the lumen of halloysite nanotubes (HNTs) in the amount of 9 wt %, and then the AT-loaded HNTs (HNTs-AT) were further incorporated into poly(vinyl alcohol)/starch composites (PVA/ST, with the weight ratio of 80/20) to construct a dual drug delivery system. AT loaded in nanotubes displayed much slower release from PVA/ST film in water than free AT; for example, the total release amount of AT from PVA/ST film with loaded AT was only 61% after 96 h, while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 47 publications
0
41
0
Order By: Relevance
“…Halloysite nanotubes (HTs) are natural aluminosilicates from a clay mineral with a hollow nanotubular structure [24,25]. HTs have been developed to use in controlled release [26], templates [27], and sorption [28] during the past decades. Recently, HTs have been successfully developed as a reinforcing filler to improve the properties of biopolymers.…”
Section: Introductionmentioning
confidence: 99%
“…Halloysite nanotubes (HTs) are natural aluminosilicates from a clay mineral with a hollow nanotubular structure [24,25]. HTs have been developed to use in controlled release [26], templates [27], and sorption [28] during the past decades. Recently, HTs have been successfully developed as a reinforcing filler to improve the properties of biopolymers.…”
Section: Introductionmentioning
confidence: 99%
“…131 Many studies have reported the ability of starch to blend with a variety of materials to advance ionotropically gelled multiple-unit systems for the enhancement of drug encapsulation, swelling, stability and controlled release of biological agents. [132][133][134][135][136] Ayorinde et al reported blends of natural starches with HPMC for orally dissolving films of amlodipine besylate (AB). They utilized Bambara nut (BAM) and the African yam bean (AYB) starches separately blended with HPMC.…”
Section: Applications Of Starch and Its Blend Derivatives In Cddssmentioning
confidence: 99%
“…HNTs can be used as a carrier for drug delivery in the medical field because of their unique hollow tubular structure, low cost, and good biocompatibility [ 12 , 20 ]. In particular, HNTs have been shown to have higher adsorption capacity than montmorillonite [ 21 ]. Moreover, it has been shown that the addition of HNTs as fillers can improve the barrier and mechanical properties of polymers [ 10 ].…”
Section: Introductionmentioning
confidence: 99%